2020
DOI: 10.3390/agronomy10050753
|View full text |Cite
|
Sign up to set email alerts
|

Strengths and Weaknesses of National Variety Trial Data for Multi-Environment Analysis: A Case Study on Grain Yield and Protein Content

Abstract: Multi-environment trial studies provide an opportunity for the detailed analysis of complex traits. However, conducting trials across a large number of regions can be costly and labor intensive. The Australian National Variety Trials (NVT) provide grain yield and protein content (GPC) data of over 200 wheat varieties in many and varied environments across the Australian wheat-belt and is representative of similar trials conducted in other countries. Through our analysis of the NVT dataset, we highlight the adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Our results showed a decreasing trend in GPC over six breeding periods in most of the environments evaluated. The negative relationship between GPC and grain yield under most environmental conditions is well known [79,80]. This result agrees well with the increase in grain yield over time, reported by our group [81] using a subset of our collection, as well as from other authors [51,53,82,83].…”
Section: Variability In Quality Traits Between Breeding Periods and Its Relationship With Allelic Variation At Glutenin Locisupporting
confidence: 92%
“…Our results showed a decreasing trend in GPC over six breeding periods in most of the environments evaluated. The negative relationship between GPC and grain yield under most environmental conditions is well known [79,80]. This result agrees well with the increase in grain yield over time, reported by our group [81] using a subset of our collection, as well as from other authors [51,53,82,83].…”
Section: Variability In Quality Traits Between Breeding Periods and Its Relationship With Allelic Variation At Glutenin Locisupporting
confidence: 92%
“…Under plant exposure to high O 3 , the observed increase in protein content is a result of the decrease in grain yield 43 , which is already simulated in some crop models 44 46 . It should be noted, however, that Eichi et al 47 found that the relationship between grain protein content and yield for wheat in Australia varies between low and high productivity environments. Hence, the linear regression of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the predicted means were used to characterise the environments using the genotype main effects (G) and genotype by environment interaction (G × E) GGE model. For the AMMI and GGE models, a balanced dataset of seven genotypes common in all the experiments was used because unbalanced datasets can affect the validity of the analysis [ 36 ].…”
Section: Methodsmentioning
confidence: 99%